2012
DOI: 10.1128/aem.00354-12
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic pH Response to Acid Stress in Individual Cells of Escherichia coli and Bacillus subtilis Observed by Fluorescence Ratio Imaging Microscopy

Abstract: ABSTRACTThe ability ofEscherichia coliandBacillus subtilisto regulate their cytoplasmic pH is well studied in cell suspensions but is poorly understood in individual adherent cells and biofilms. We observed the cytoplasmic pH of individual cells using ratiometric pHluorin. A standard curve equating the fluorescence ratio with pH was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 38 publications
7
131
1
1
Order By: Relevance
“…All cells regulate their cytosolic pH due to the inherent pH dependence of biochemical reactions (27). However, cytosolic pH varies substantially between organisms and growth conditions (28,29). Here, we use a mathematical model to examine how the cyanobacterial CCM functions over a range of cytosolic pH values.…”
Section: Resultsmentioning
confidence: 99%
“…All cells regulate their cytosolic pH due to the inherent pH dependence of biochemical reactions (27). However, cytosolic pH varies substantially between organisms and growth conditions (28,29). Here, we use a mathematical model to examine how the cyanobacterial CCM functions over a range of cytosolic pH values.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other experiments demonstrated that cell homeostasis responses [86][87][88], and the recombinant protein production process occur in a similar time order [99]. Then, we can hypothesize that during those cell responses, cellular microenvironments favor the nucleation and formation of proto-aggregates, which later allow the formation of IBs.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic pH is normally maintained within a range of 7.4 to 7.8 when the external pH is in the range of 5.0 to 9.0 in suspension or 5.0 to 8.0 in adherent E. coli cultures [56,[85][86][87][88]. In adherent E. coli cultures the cytoplasmic pH is similar to the external pH of 8.5 to 9.0 [87].…”
Section: Discussionmentioning
confidence: 99%
“…The pH-sensitive polar fluorescein derivative 2 0 ,7 0 -bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein, acetoxymethyl ester (BCECF) remains the most widely used pHi indicator. However, experimental limitations imposed by pH-sensitive dyes have more recently led to the development of genetically encoded pH biosensors derived from the jellyfish Aequorea victoria green fluorescent protein (GFP; Martinez et al, 2012;Miesenböck, De Angelis, & Rothman, 1998;Wilks & Slonczewski, 2007). Together, these pH-sensitive dyes and biosensors can be imaged using most standard fluorescence microscopes to measure steadystate and dynamic changes in pH within cells.…”
Section: Currently Used Ratiometric Ph Probesmentioning
confidence: 99%
“…In general, cytoplasmic pH in most organisms from bacteria (Martinez et al, 2012;Wilks & Slonczewski, 2007) to yeasts (Bagar, Altenbach, Read, & Bencina, 2009;Grynkiewicz et al, 1985) to mammalian cells (Fig. 23.1) is slightly basic (pH is $7.0-7.8), with the exception of some acidophilic or basophilic bacteria (Paradiso et al, 1984;Slonczewski, Fujisawa, Dopson, & Krulwich, 2009).…”
Section: Subcellular Ph Measurementsmentioning
confidence: 99%